Screening biotoxin aptamer and their application of optical aptasensor in food stuff: a review - Sun, Jiefang; Zhang, Meng; Gao, Qianlong; Shao, Bing (Frontiers in Chemistry, 2024)
Biotoxins are ranges of toxic substances produced by animals, plants, and microorganisms, which could contaminate foods during their production, processing, transportation, or storage, thus leading to foodborne illness, even food terrorism. Therefore, proposing simple, rapid, and effective detection methods for ensuring food free from biotoxin contamination shows a highly realistic demand. Aptamers are single-stranded oligonucleotides obtained from the systematic evolution of ligands by performing exponential enrichment (SELEX). They can specifically bind to wide ranges of targets with high affinity; thus, they have become important recognizing units in safety monitoring in food control and anti-terrorism. In this paper, we reviewed the technical points and difficulties of typical aptamer screening processes for biotoxins. For promoting the understanding of food control in the food supply chain, the latest progresses in rapid optical detection of biotoxins based on aptamers were summarized. In the end, we outlined some challenges and prospects in this field. We hope this paper could stimulate widespread interest in developing advanced sensing systems for ensuring food safety.